Trends and correlates of HIV testing amongst women: lessons learnt from Kenya - Thomas N.O. Achia; Eunice Obayo (AOSIS, 2013)
Background: A majority of women in Kenya do not know their HIV status and are therefore unable to take preventive measures or medication in order to prolong their lives. Objectives: This study investigates the key determinants of HIV testing in Kenya and documents how these changed over the 1998-2008 period. Method: This study uses data from the 1998, 2003 and 2008 Kenya Demographic and Health surveys. Principal components analysis was used to compute indices of HIV knowledge, HIV-related stigma, media exposure and decision making. Survey logistic regression analysis was used to determine factors that had a statistically-significant association with ever having been tested for HIV. Results: Testing was significantly higher in 2008 compared with the previous surveys. In 1998, 14.7% of the women had tested for HIV. The rate increased to 15.0% in 2003 and then to 59.2% in 2008. In the 1998 and 2003 Kenya Demographic and Health surveys, respondents' age, region of residence, education, knowledge of someone who had died from HIV-related illness and media exposure were the main determinants of testing. In the 2008 study, HIV-related stigma, occupation and the partner's level of education were found to be associated with HIV testing. Conclusion: Despite efforts to scale up voluntary counselling and testing in Kenya over the 1998-2008 period, HIV testing amongst women is still quite low. Prevention and control programmes in Kenya need to focus on reducing HIV-related stigma, increasing access to testing in rural areas and increasing access amongst women with little or no education.